(untitled) (Anwer Khan Modern Medical College Journal, 2011)
Dietary nutrients have shown overriding influence on insulin sensitivity and secretory status of diabetic subjects due to rapid lifestyle changes and urbanization. A case control study was conducted with 98 type 2 diabetic subjects and 97 healthy controls with BMI below obesity range to explore the association of dietary carbohydrate and body insulin status of nonobese diabetic subjects. Nutrient profile was taken by dietary recall method. Homeostasis Model Assessment (HOMA) was applied for measuring insulin status. Laboratory analysis and anthropometric measurements were done by standard methods. Statistical analysis was performed. Significant insulin secretory defect was found in diabetic group [Median (range), %; Control, 153 (65-285); DM, 50 (4-269)]. In diabetic group total carbohydrate [Median (range), gm/d; control, 235 (102-422); DM, 292 (151-454)], and fiber [Median (range), gm/d; control, 4.5 (2-18); DM, 6.2 (1.5-21)] consumption were found to be significantly higher than control. But no significant association was established between insulin secretions (HOMA%B) with carbohydrate consumption among the case group. So carbohydrate consumption does not influence β- cell serectory dysfunction in nonobese T2 DM patients. The possible potential effect of carbohydrate in insulin depression is not established. Key Words: Dietary Carbohydrate; Insulin Secretion; Nonobese Type 2 Diabetics DOI: http://dx.doi.org/10.3329/akmmcj.v2i2.8166 AKMMC J 2011; 2(2): 14-17